Volume Transport Time Series and Variability of the North Atlantic Eastern Boundary Current at Goban Spur. Issue 9 (16th September 2021) - Moritz, Martin; Jochumsen, Kerstin; Kieke, Dagmar; Klein, Birgit; Klein, Holger; Köllner, Manuela; Rhein, Monika
Abstract: The Eastern Boundary Current is an essential part of the water mass exchange between the subtropical and subpolar North Atlantic. Here, we study the offshore branch of the European Shelf Current (ESC) over the Goban Spur slope area off Ireland. Our analysis is based on current measurements obtained from a multiyear mooring effort, complemented by ship‐board observations along a hydrographic section, satellite‐derived estimates of absolute dynamic topography with geostrophic currents, and float trajectories. These data serve to quantify the offshore branch of the ESC on intraannual to interannual timescales. From the moored observations, we derive a mean poleward along‐slope volume flux of 3.7 ± 0.7 Sv for the period 2017–2019. Using a multilinear regression model and geostrophic surface velocities, we extend the time series to the period 1993–2019 and obtain a long‐term mean transport of 3.2 ± 0.4 Sv. Both time series show strong variability ranging from −7.5 to 15.7 Sv. The variability is linked to a dynamic eddy field, especially a stationary cyclonic circulation pattern near the mooring array, and meandering of current branches originating from the North Atlantic Current. We find no evidence of a consistent deep boundary current extending from the shelf break to the position of the offshore mooring (4, 500 m depth), but confirm a persistent along‐slope flow at the shallower slope (1, 500 m depth). Geostrophic surface velocities and float trajectories reveal that the offshore branch of the ESC does not follow a clear northward path from the eastern subtropical regions but rather indicate the intermittent character of the flow. Plain Language Summary: In this study, we describe the European Shelf Current (ESC) in the eastern North Atlantic. The study area is the deeper part of the Goban Spur area off Ireland. We use current measurements of instruments deployed in the water column from 2016 to 2019 combined with satellite observations of surface circulation and drifting float paths. We aim to quantify the contribution of the offshore branch to the ESC system. We calculate a poleward volume transport following the slope that is on average 3.7 ± 0.7 Sverdrup (Sv; 1 Sv = 1 million cubic meter per second) for the period 2017–2019. We use a mathematical relation between mooring data and satellite observations to extend the time series to the period 1993–2019 and obtain an average transport of 3.2 ± 0.4 Sv. There occur strong changes over time ranging from −5 to 15 Sv. These changes are caused by rotating vortices (eddies), especially a counter‐clockwise rotating circulation pattern near the moorings, and changing positions of currents branching from the North Atlantic Current. We find that the offshore branch of the ESC does not follow a clear northward path from the eastern subtropical regions of the North Atlantic. Instead, the flow is of rather unsteady character. Key Points: The analysis of multiplatform observational efforts is used to study the circulation at the North Atlantic Eastern Boundary The volume transport of the offshore branch of the European Shelf Current is on average 3.2 ± 0.4 Sv for the period 1993–2019 Transport variability is in the range of −7.5–15.7 Sv and induced by eddies and meandering North Atlantic Current branches